High thermoelectric performance of n-type PbTe1−ySy due to deep lying states induced by indium doping and spinodal decomposition. (April 2016) - Zhang, Qian; Chere, Eyob Kebede; Wang, Yumei; Kim, Hee Seok; He, Ran; Cao, Feng; Dahal, Keshab; Broido, David; Chen, Gang; Ren, Zhifeng
Abstract: Good thermoelectric materials should have high engineering figure-of-merit ( ZT ) eng, not peak ZT, to achieve high conversion efficiency. In this work, we achieved a good ( ZT ) eng by optimizing the carrier concentration to improve the room temperature ZT using deep lying dopant, indium, in PbTe1− y S y . It was found that a room temperature ZT as high as ~0.5 and a peak ZT ~1.1 at about 673 K were obtained in Pb0.98 In0.02 Te0.8 S0.2 due to a lower thermal conductivity by alloy scattering and Spinodal decomposition. The calculated efficiency could be as high as ~12% at cold side 323 K and hot side 773 K. The approach is expected to work in other materials systems too. Graphical abstract: We have achieved increased average ZT and high conversion efficiency ~12% at cold side 323 K and hot side 773 K by optimizing the carrier concentration to improve the room temperature ZT using deep lying dopant, indium, in PbTe1− y S y and lowered the lattice thermal conductivity through alloy scattering and Spinodal decomposition. Highlights: PbS was incorporated into In-doped PbTe to increase the electrical conductivity. Optimization of room temperature ZT by deep lying doping leads to high average ZT . Thermal conductivity was reduced by alloy scattering and spinodal decomposition. High conversion efficiency ~12% was achieved at cold side 323 K and hot side 773 K.